The SNARE protein Vti1b is recruited to the sites of BCR activation but is redundant for antigen internalisation, processing and presentation - Music, Amna; Tejeda-González, Blanca; Cunha, Diogo M.; Fischer von Mollard, Gabriele; Hernández-Pérez, Sara; Mattila, Pieta K. (Frontiers in Cell and Developmental Biology, 2022)
In order to fulfil the special requirements of antigen-specific activation and communication with other immune cells, B lymphocytes require finely regulated endosomal vesicle trafficking. How the endosomal machinery is regulated in B cells remains largely unexplored. In our previous proximity proteomic screen, we identified the SNARE protein Vti1b as one of the strongest candidates getting accumulated to the sites of early BCR activation. In this report, we follow up on this finding and investigate the localisation and function of Vti1b in B cells. We found that GFP-fused Vti1b was concentrated at the Golgi complex, around the MTOC, as well as particularly in the Rab7+ lysosomal vesicles in the cell periphery. Upon BCR activation with soluble antigen, Vti1b showed partial localization to the internalized antigen vesicles, especially in the periphery of the cell. Moreover, upon BCR activation using surface-bound antigen, Vti1b polarised to the immunological synapse, colocalising with the Golgi complex, and with lysosomes at actin foci. To test for a functional role of Vti1b in early B cell activation, we used primary B cells isolated from Vit1b-deficient mouse. However, we found no functional defects in BCR signalling, immunological synapse formation, or processing and presentation of the internalized antigen, suggesting that the loss of Vti1b in B cells could be compensated by its close homologue Vti1a or other SNAREs.